Salvage versus amputation: Utility of mangled extremity severity score in severely injured lower limbs - Kumar, M Kiran (Medknow Publications, 2007)
BACKGROUND: The purpose of the present study was to evaluate the clinical utility of Mangled extremity severity score (MESS) in severely injured lower limbs. MATERIALS AND METHODS: Retrospectively 25 and prospectively 36 lower limbs in 58 patients with high-energy injuries were evaluated with the use of MESS, to assist in the decision-making process for the care of patients with such injuries. Difference between the mean MESS scores for amputated and salvaged limbs was analyzed. RESULTS: In the retrospective study 4.65 (4.65 ± 1.32) was the mean score for the salvaged limbs and 8.80 (8.8 ± 1.4) for the amputated limbs. In the prospective study 4.53 (4.53 ± 2.44) was the mean score for the salvaged limbs and 8.83 (8.83 ± 2.34) for the amputated limbs. There was a significant difference in the mean scores for salvaged and amputated limbs. Retrospective 21 (84%) and prospective 29 (80.5%) limbs remained in the salvage pathway six months after the injury. CONCLUSION: MESS could predict amputation of severely injured lower limbs, having score of equal or more than 7 with 91% sensitivity and 98% specificity. There was a significant difference in the mean MESS scores in the prospective study (n=36), 4.53 (4.53 ± 2.44) in thirty salvaged limbs (83.33%) and 8.83 (8.83 ± 2.34) in six amputated limbs (16.66%) with a P-value 0.002 (P-value < 0.01). Similarly there was a significant difference in the mean MESS score in the retrospective study (n=25), 4.65 (4.65 ± 1.32) in twenty salvaged limbs (80%) and 8.80 (8.8 ± 1.4) in five amputated limbs (20%) with a P-value 0.00005 (P-value < 0.01). MESS is a simple and relatively easy and readily available scoring system which can help the surgeon to decide the fate of the lower extremity with a high-energy injury.